2009
DOI: 10.1103/physrevb.80.224204
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study on internal friction in an Al-Pd-Mn icosahedral quasicrystal and its crystal approximants

Abstract: The internal friction was measured for an Al-Pd-Mn icosahedral phase ͑i-phase͒ and its 1/1 and 2/1 approximant phases in an Al-Pd-Mn-Si system in a forced flexural-oscillation mode in a frequency range of 0.05-20 Hz and a temperature range of 300-873 K. For the i-phase, large and small absorption peaks were observed with Q −1 Ϸ 1.3ϫ 10 −2 and 8 ϫ 10 −4 , respectively. These two peaks were absent for the 1/1-phase, which showed two other peaks instead. The 2/1-phase exhibited the features of both the i and 1/1-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…The peak heights of Q ¹1 experimentally obtained for AgInYb, AlPdMn 9) and AlCuFe 10) i-phases are summarized in Table 1. The effective elastic constants I, c and K change with changing the directions of the wavevector q and the wave polarization p of the elastic phonon wave given to the system.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The peak heights of Q ¹1 experimentally obtained for AgInYb, AlPdMn 9) and AlCuFe 10) i-phases are summarized in Table 1. The effective elastic constants I, c and K change with changing the directions of the wavevector q and the wave polarization p of the elastic phonon wave given to the system.…”
Section: Resultsmentioning
confidence: 99%
“…Later, So and his coworkers 9) performed a comparative study on the internal friction of an i-AlPd Mn and its 1/1 and 2/1 crystal approximant phases. The results showed that the behavior of the internal friction systematically changes in the order of 1/1-, 2/1-and i-phases.…”
Section: )mentioning
confidence: 99%